The Role of Social Support in Participation Perspectives of Caregivers of Children with Intellectual Disabilities in India and South Africa - Dada, Shakila (Int J Environ Res Public Health, 2020)
Caregivers are an intrinsic component of the environment of children with intellectual disabilities. However, caregivers’ capacity to support children’s participation may be linked to the social support that they, as caregivers, receive. Social support may increase participation, educational, psychological, medical and financial opportunities. However, there is a lack of information on social support in middle-income countries. The current study described and compared the social support of caregivers of children with intellectual disabilities by using the Family Support Survey (FSS) in India and South Africa. The different types of social support were subsequently considered in relation to participation, using the Children’s Assessment of Participation and Enjoyment (CAPE). One hundred caregiver–child dyads from India and 123 from South Africa participated in this study. The data were analysed using non-parametric measures. Indian caregivers reported greater availability of more helpful support than did the South African caregivers. Social support was associated with children’s participation diversity (India) and intensity (South Africa). The child-/caregiver-reported participation data showed different associations with participation. Results from this study suggest that perceived social support of caregivers differs between countries and is associated with their child’s participation. These factors need to be considered when generalising results from different countries.